Survey of Campus Incidents as Interpreted by College Presidents, Faculty Chairmen and Student Body Presidents, 1970 ([Verlag nicht ermittelbar], 1984)
This study was conducted in the summer of 1970 following the invasion of Cambodia in May 1970. Presidents, faculty chairmen, and student body presidents of all accredited colleges and universities in the United States were queried about the types of incidents that occurred on their campuses. These included incidents in which the National Guard was called, off-campus police were used, one or more protestors were arrested, temporary restraining orders or injunctions were obtained, teach-ins, rallies, or discussion groups took the place of regular academic activities, and where Black demands or racism were raised as issues. Other incidents examined were those involving destructive acts by students that took place off-campus and incidents involving serious damage to or the destruction of property, personal injury, or death. The seriousness of the incidents was reported as well as the response of the faculty, administration, and outside government units. The respondents were asked what plans were prepared before May of 1970 to handle unrest, and the degree to which these were implemented, as well as their proposals to curb or limit future outbreaks. The data include information on the school, such as location, size, sex of students, presence of ROTC on campus, academic emphasis, acceptance standards, and dollars expended per student.